Faktor-Faktor Yang Berhubungan Dengan Pemberian ASI Ekskluif Pada Ibu Baduta Di RSIA Budi Kemuliaan Jakarta - Azhari, Anna Sundari; Pristya, Terry Y.R. (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2019)
Based on Indonesia Health Profile year 2017 obtained equal to 46,60% infants who get exclusive breastfeeding until 6 months, but target exclusive breastfeeding nationally is equal to 80%. Health care facilities such as hospitals play a role in supporting the realization of national achievements. The purpose of this research is to know the factors associated with exclusive breastfeeding in mother Baduta in Women and Children Hospital Budi Kemuliaan Jakarta. The research method is analytical with cross sectional design using purposive sampling technique. Research subjects were 50 respondents with the criteria of mothers who have babies aged 6 – 24 months as outpatients who visited the Children Polyclinic at Women and Children Hospital Budi Kemuliaan Jakarta. Data analysis using chi-square test. The results showed that there was significant relationship between lactation information with p-value = 0,010 and OR = 6,781, infant health condition with p-value = 0,048 and OR = 5,167, and husband and family support with p-value = 0,040 and OR = 4,571 with exclusive breastfeeding. The Conclusion is from fifteen variables in the analysis there are three related variables of lactation information, infant health condition, and support of husband and family.